Selection and validation of stable reference genes in potato infected by Pectobacterium atrosepticum using real-time quantitative PCR - Lijuan Hou; Haixia Zhu; Wenrong Xian; Yongqiang Ma (Scientific Reports)
Abstract Potato blackleg disease is caused by Pectobacterium atrosepticum, can seriously destroy potatoes’ growth and development. To accurately evaluate the expression levels of genes involved in potato (Solanum tuberosum) responses to P. atrosepticum infection, seven candidate reference genes (EF1α, eIF5A3, Tubulin, Ubiquitin, GAPDH, Actin, and CYP3) were systematically assessed for their expression stability at 1, 3, and 5 days after inoculation (dai) using the geNorm, NormFinder, BestKeeper, ∆Ct, and RefFinder algorithms. The results demonstrated that EF1α exhibited the highest stability among all experimental conditions, followed by eIF5A3 and Tubulin, whereas Ubiquitin displayed the least stability. To validate the screening outcomes, the expression patterns of four disease resistance-related genes (RBOHC, WRKY24, MPK3, and CPK32) were analyzed in both resistant and susceptible potato cultivars using the EF1α as the most stable and Ubiquitin as the least stable. Validation experiments revealed that the expression levels of disease resistance-related genes were stable and consistent with the RNA-Seq data when EF1α was used as a reference gene. In contrast, using Ubiquitin as a reference gene led to significant variability. Therefore, EF1α can be employed as the reference gene when studying the interaction between the potato and P. atrosepticum, providing a standardized reference for the subsequent studies on screening of disease resistance genes and exploring of disease resistance mechanism in potato.